Petrogenesis, Redox State, and Mineralization Potential of Triassic Granitoids in the Mengshan District, South China - Yang, Yanshen; Pan, Xiaofei; Hou, Zengqian; Deng, Yang; Ouyang, Yongpeng; Meng, Delei; Xie, Tao (Frontiers in Earth Science, 2021)
The Mengshan district is located in the eastern segment of the Jiangnan Orogen in South China. Multi-phase intrusions were emplaced in this district, with the medium-grained porphyritic biotite granite and its marginal phase (fine-grained porphyritic biotite granite) genetically related to metal and non-metal mineralization. In this study, zircon U–Pb ages and trace elements, whole-rock geochemistry, and Nd isotopes were systematically analyzed for medium- and fine-grained porphyritic biotite granite in the Mengshan district, with the aim of elucidating the origin, evolutionary process, redox state, and mineralization competency of the studied granites. The Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LA–ICP–MS) zircon U–Pb dating provided a weighted mean age of 226.6 ± 0.5 to 225.9 ± 0.5 Ma for the studied Mengshan granites, synchronous with the late-episode Triassic magmatism-mineralization in South China. The studied Mengshan granites are high-Si and -K, low-P, and weakly peraluminous, exhibiting features of highly evolved I-type granites. The detailed whole-rock geochemistry and Nd isotopes, and zircon trace elements and Hf isotopes demonstrated that the studied Mengshan granites were likely derived from disequilibrium melting of Proterozoic metamorphic basements that were composed of meta-igneous and metasediments and underwent fractional crystallization of plagioclase, K-feldspar, biotite, Fe-Ti oxide, zircon, and apatite. Low whole-rock K/Rb (<150), Nb/Ta (<6), and Zr/Hf (<26) ratios and the metasomatized rim of zircon also suggest that the melt–fluid interaction occurred during the formation of more evolved fine-grained porphyritic biotite granite. The Mengshan granites have a relatively reduced redox state, revealed by their relatively low whole-rock Fe2O3/FeO ratios (mostly < 0.5), zircon Ce4+/Ce3+ ratios (mostly lower than 90), and oxygen fugacity (below ΔFMQ + 1.4). The data in this study indicate that the Mengshan granites, especially the more evolved fine-grained porphyritic biotite granite, are favorable for W, Sn, Mo (<0.3 Mt), and Cu (<1 Mt) mineralization. Moreover, the contact zone between the fine-grained porphyritic biotite granite (or other Triassic granites) and the Permian Maokou Formation (flint-nodule limestone) is a potential target region for wollastonite exploration.